2004
DOI: 10.1111/j.1365-2036.2004.02267.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: the treatment of irritable bowel syndrome

Abstract: Summary To evaluate therapies available for the treatment of irritable bowel syndrome, and provide consensus recommendations for their use, a total of 51 double‐blind clinical trials using bulking agents, prokinetics, antispasmodics, alosetron, tegaserod and antidepressants were selected. The quality of studies was assessed using 5‐point scale. Meta‐analyses were performed on all studies, and on ‘high‐quality studies’. The efficacy of fibre in the global irritable bowel syndrome symptoms relief (OR: 1.9; 95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(132 citation statements)
references
References 193 publications
(195 reference statements)
7
121
0
4
Order By: Relevance
“…In another meta-analysis of 13 placebo-controlled studies, fiber was found to improve global symptoms of IBS. But after exclusion of low-quality studies, the result did not reach statistical significance [122] . Abnor mal bacterial fer mentation and disturbed gas handling may also cause bloating and abdominal pain and may worsen clinical outcome [141] .…”
Section: Bulking Agentsmentioning
confidence: 94%
See 1 more Smart Citation
“…In another meta-analysis of 13 placebo-controlled studies, fiber was found to improve global symptoms of IBS. But after exclusion of low-quality studies, the result did not reach statistical significance [122] . Abnor mal bacterial fer mentation and disturbed gas handling may also cause bloating and abdominal pain and may worsen clinical outcome [141] .…”
Section: Bulking Agentsmentioning
confidence: 94%
“…mebeverine, pinaverine, octylonium bromide). Most studies of smooth muscle relaxants have been hindered by poor study design, high drop-out rates, and low patient enrollment which have made assessment of their therapeutic value in IBS difficult [121][122][123] . In a recent meta-analysis, only octylonium bromide was found to have some benefit after excluding poor quality studies [122] .…”
Section: Antispasmodicsmentioning
confidence: 99%
“…Most published studies have shown that TCAs improve the symptoms in FGID patients; however, the quality and design of these trials has been variable. [44][45][46][47][48] Of the three recent meta-analyses that have evaluated the possible beneficial effects of TCAs on functional GI symptoms, two concluded that such treatments were beneficial, 49,50 while one concluded that they were not superior to placebo, for the treatment of IBS. 51 Jackson et al 49 were of poor quality and that TCAs were not superior to placebo for global GI symptom improvement.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%
“…[20][21][22] These trials are characterized by a low methodological quality and the heterogeneity of the populations recruited in these trials, leading to contradictory conclusions. 23 Antispasmodic efficacy to improve abdominal pain in IBS remains a matter of debate. To avoid these methodological criticisms, our study was designed in accordance with the 'points to consider' on the evaluation of drugs for the treatment of IBS and followed the recommended criteria for methodological good quality.…”
Section: Discussionmentioning
confidence: 99%